Intellectual capital and performance measurement systems in Iran - Asiaei, Kaveh; Jusoh, Ruzita; Bontis, Nick (Emerald, 2018)
Purpose: The purpose of this paper is to empirically explore how the effect of intellectual capital (IC) on organizational performance is indirect and mediated through performance measurement (PM) systems. Design/methodology/approach: Data were collected from a survey of 128 chief financial officers of Iranian publicly listed companies. Hypotheses were tested using partial least squares regression, a structural modeling technique which is appropriate for highly complex predictive models. Findings: Results from the structural model indicate that, in general, companies with a higher level of IC place a premium on the balanced use of PM systems in a diagnostic and interactive style. Furthermore, the results provide some evidence that IC is indirectly associated with organizational performance through the intervening variable of the balanced use of interactive and diagnostic PM systems. Practical implications: This study sheds light on the issue of how senior management should use PM systems to take full advantage of intellectual assets which could lead to improved organizational performance. Originality/value: This is the first study of its kind to synthesize a model which examines IC, PM systems, and organizational performance. Although the effect of different types of intangible assets on performance has been substantially examined in the literature, less effort has been devoted to understanding the role of PM systems in leveraging an organization’s IC.